Orientalism in Updike's Terrorist - Tahseen Ali M., Malik Oufi Jasim Al-Maliki, Seriaznita Binti Haji Mat Said, (Opción, 2019)
The title of the study aims to explore the concept of Orientalism from a selected western novel by Updike entitled Terrorist via comparative qualitative research methods. As a result, the Orient should not be educated and should be under the hegemony of the Westerners. The Orient should be under the influence of Europocentrism, however, not all the attempts by the West had succeeded. In conclusion, through Sheikh Rashid's interpretation of the Holy Quran, Ahmad was convinced to follow the terrorist’s path.